Ultralow pressure membrane filtration for water and wastewater treatment - Leong, C.L. (Elsevier, 2023)
Ultralow pressure membrane filtration (ULPMF) has been explored for over 10years. It shifts the paradigm in the operation of membrane filtration. Traditionally, the membrane is regularly cleaned to allow application of high transmembrane pressure (ÎP). On the other hand, ULPMF does not employ chemical cleaning and operates under ultralow pressure of <0.1bar, driven by gravity and befriends the (bio)fouling. The biofilm is preserved atop the membrane surface, which eventually controls the flux stabilization. It was initially developed to supply drinking water, but has also been explored for different applications. This chapter outlines the state of the art and the implementation of ULPMF. Next, the characteristics of the ULPFM system, mainly on the rationale behind the flux stabilization and the biofilm-aided filtration, are discussed. Subsequently, factors affecting the stable flux, organic removals/rejection, and biofilm ecosystem are outlined. Finally, the sustainability issue and perspectives on the further developments of the system are outlined. Â© 2023 Elsevier Inc. All rights reserved.